(untitled) (Global Journal of Management and Business Research, 2014)
E-business is a new revolution where initiative is needed to fully utilize the capabilities of Internet technology in a specific business setting. Such an initiative has built the fundamental strengths of the organization that creates a huge competitive advantage among the competitors in the market. In this paper, a method is presented for the development of an e-business which is based on the research of value creation, reward or creating promotions for customers to build a strong trust between company and customers, and also knowledge management. The proposed method is designed to help clarify a strategic e-business vision and to solicit management commitment to change and take action on new business opportunities. In addition, it also impacts the environment positively through the societal world demand of moving rapidly in the direction of valuing low-pollution and energy-efficient products.